2011
DOI: 10.1517/17425247.2011.628656
|View full text |Cite
|
Sign up to set email alerts
|

Results from the single-use autoinjector for self-administration of subcutaneous interferon beta-1a in patients with relapsing multiple sclerosis (MOSAIC) study

Abstract: The single-use autoinjector was well received and supported by favorable ratings for simplified injections and convenience. The results suggest that the device may improve overall injection experience in patients with relapsing MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Only 3.8% of patients reported ISRs and 13.8% experienced one or more event of injection site erythema, pain, or reaction, which is lower than the 29.6 --43.3% incidence of ISRs reported in studies of serum-free sc IFN b-1a administered by manual injection or a mechanical autoinjector [34,35,[41][42][43]. In 12-week user trials of the autoinjector, most patients reported that reactions or pain at the injection site were equally or less problematic than with their previous mechanical autoinjector [32], with almost a quarter of patients citing 'less injection pain' as the second most attractive feature of the device after 'convenience' [27].…”
Section: Discussionmentioning
confidence: 69%
“…Only 3.8% of patients reported ISRs and 13.8% experienced one or more event of injection site erythema, pain, or reaction, which is lower than the 29.6 --43.3% incidence of ISRs reported in studies of serum-free sc IFN b-1a administered by manual injection or a mechanical autoinjector [34,35,[41][42][43]. In 12-week user trials of the autoinjector, most patients reported that reactions or pain at the injection site were equally or less problematic than with their previous mechanical autoinjector [32], with almost a quarter of patients citing 'less injection pain' as the second most attractive feature of the device after 'convenience' [27].…”
Section: Discussionmentioning
confidence: 69%
“…In the first few months of IFNB treatment, when side effects tend to be more prevalent, many efforts can be made to improve the patients' adherence, such as dose titration, concomitant prophylactic therapy, use of autoinjectors, patient education, supporting programs [19,20,21,22,23]. By contrast, there are currently no established strategies to manage problems related to long-term adherence and persistence, especially forgetting or tiredness of taking injections [8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the consistency of these outcomes with those reported in Year 1 of the ADVANCE study lends support to the direction of the findings reported here. Data from this sub-study also compare well with tolerability and satisfaction data reported using other IFN self-injection devices [10][11][12][13][14][15][16][17][18]. In a 12-month open-label observational Phase IV study, 213 intent-to-treat patients self-administered 30 µg intramuscular IFN-b 1a once weekly via an autoinjector pen.…”
Section: Patients (%)mentioning
confidence: 62%
“…In a 6-month interim analysis, > 95% of patients reported being satisfied or very satisfied with the autoinjector, and reported injection fear and anxiety decreased between day 1 and month 6 [11]. Although these studies cannot be directly compared with the current study given the differences in form of IFN, formulation, dose and frequency, in addition to differences in study designs and patient populations, a common theme across the studies is that autoinjectors improve patient satisfaction/ease-of-use [10][11][12][13][14][15][16][17][18], with further evidence of > 95% of patient-reported adherence after 6 months of IFN-b 1a administration via an autoinjector [11]. In the ADVANCE study, patient compliance was > 99% in all study arms [7].…”
Section: Patients (%)mentioning
confidence: 99%